Experimental and theoretical research on the fire safety of a building insulation material via the ignition process study - Yufeng Huang; Yufeng Li (Case Studies in Thermal Engineering, 2018)
A series of experiments were carried out on extruded polystyrene (XPS) foam using a vertical thermal radiator. Measurements were taken for the ignition time, the pyrolysis mass and the temperature distribution. Two kinds of XPS foam with flame retardant levels of B1 and B2 were tested in the experiments and the incident heat fluxes were set as 20, 30, 35, 40, 50 and 60 kW/m2. For the XPS shrinks to a thin layer under the thermal radiator heating, thus the classical ignition theory may be improper and the new functions relationship between the ignition time and the radiant heat flux was derived in theory and experiment. What's more, the pyrolysis mass increases with the radiant heat flux, while the extent of increasing reduces as the radiant heat flux increases. And the result of temperature distribution indicated that under high incident heat flux the flame retardant treatment becomes less effective. The research results were useful for the theory and the experimental study on the fire characteristic of foamed polymer under vertical radiation condition. Keywords: Safety engineering, Thermal insulation material, Vertical radiation, Ignition, XPS, Ignition model